Constitutive expression in gal7 mutants of Kluyveromyces lactis is due to internal production of galactose as an inducer of the Gal/Lac regulon. - Cardinali, G (1997)
The induction process of the galactose regulon has been intensively studied, but until now the nature of the inducer has remained unknown. We have analyzed a delta gal7 mutant of the yeast Kluyveromyces lactis, which lacks the galactotransferase activity and is able to express the genes of the Gal/Lac regulon also in the absence of galactose. We found that this expression is semiconstitutive and undergoes a strong induction during the stationary phase. The gal1-209 mutant, which has a reduced kinase activity but retains its positive regulatory function, also shows a constitutive expression of beta-galactosidase, suggesting that galactose is the inducer. A gal10 deletion in delta gal7 or gal1-209 mutants reduces the expression to under wild-type levels. The presence of the inducer could be demonstrated in both delta gal7 crude extracts and culture medium by means of a bioassay using the induction in gal1-209 cells. A mutation in the transporter gene LAC12 decreases the level of induction in gal7 cells, indicating that galactose is partly released into the medium and then retransported into the cells. Nuclear magnetic resonance analysis of crude extracts from delta gal7 cells revealed the presence of 50 microM galactose. We conclude that galactose is the inducer of the Gal/Lac regulon and is produced via UDP-galactose through a yet-unknown pathway.